Integrasi Budaya Lokal dan Media Interaktif Genially dalam Pembelajaran Ekonomi: Analisis Kebutuhan Pengembangan Media Untuk Meningkatkan Literasi Keuangan Peserta Didik SMA - fitri yanti; Dewi Pratita; Sari Meilani Tirta (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2025)
This study aims to analyze the need for developing local culture-based economic learning media in South Sumatra using the Genially digital platform to improve the financial literacy of high school students. This quantitative descriptive study involved economics teachers and high school students at Srijaya Negara High School as respondents through a Likert scale questionnaire covering four aspects: learning media needs, local culture integration, financial literacy, and readiness for Genially. The data were analyzed using descriptive statistics with average score calculations. The results showed a very high need (score of 4.4 for teachers) and 4.3 (high) for students) for interactive learning media that integrates the local cultural context into economic learning. The integration of local culture, such as family gatherings, the habit of saving gold, songket, and land in South Sumatran society, was considered effective as a bridge for contextualizing abstract economic concepts through the Contextual Teaching and Learning (CTL) approach. Although familiarity with Genially was still low, interest in adoption was very high (4.60), and the need for assistance reached a score of 4.75. This study recommends the development of Genially-based digital media that integrates ethnopedagogy as an innovative solution to improve contextual financial literacy, accompanied by a structured and sustainable teacher capacity building program.